Dynamic Optimization Algorithm of Wireless Sensor Network - Yong Ding (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper analyzes the existing real network and modeled dynamic optimization of wireless sensor network; it realizes the integration of node deployment and selection, and sets the optimization parameters. The simulation experiment shows the proposed algorithm with better optimization fitness value and less evolutionary generation, it balanced the wireless sensor network node energy consumption, improved network coverage and reduced network energy consumption and prolongs the network lifetime. http://dx.doi.org/10.11591/telkomnika.v12i9.4863